First evidence of microplastics in freshwater from fish farms in Rondônia state, Brazil - Jerônimo Vieira Dantas Filho; Vinícius Perez Pedroti; Bruna Lucieny Temponi Santos; Maria Mirtes de Lima Pinheiro; Átila Bezerra de Mira; Francisco Carlos da Silva; Emerson Carlos Soares e Silva; Jucilene Cavali; Elica Amara Cecilia Guedes; Sandro de Vargas Schons (Heliyon, 2023)
The main aimed of this study was to provide information on microplastics present in the freshwater of fish farm ponds. In addition, the study showes a relationship between the seasonal, spatial distribution and the amount of microplastics found. This study was conducted in 35 fish farms located in the Rondônia state, Brazil, the sample collects were carried out in the two Amazonian hydrological seasons (dry and rainy). The study was developed in a completely randomized factorial scheme 35 × 3 x 3 (35 fish farms, 3 ponds and 3 repetitions per ponds). Microplastic sampling was performed following a modified method based on National Oceanic and Atmospheric Administration (NOAA). Samples of 250 mL freshwater collected, which were deionized and pre-filtered through 6.0 mm mesh granulometric sieves. The average abundances of the different hydrological seasons were compared by Student's t-test, with differences statistically significant at p < 0.05. The microplastics were morphological categorized into fibers and colors blue, red or transparent. Microplastic contamination was confirmed in freshwater of 9 fish farming, with greater abundance of blue fibers and greater quantification in the rainy season. Fish farms P3, P4 and P6 had the highest quantifications of blue fiber in the two seasons (6 and 43, 19 and 56, 11 and 88 items mL−1, respectively). Almost all fish farms had a higher abundance of microplastics in the rainy season. It is important to highlight the prominence of microplastics in the blue fiber rainy season (286 items mL−1) compared to the dry season (58 items mL−1). Fish farms P3, P4 and P6 showed a strong positive correlation between the factors distance from the nearest urban area (r = 0.94, 0.79 and 0.97, respectively) and seasonality (r = 0.98, 0.77 and 0.96, respectively). Rainfall variations influenced the abundance of microplastics, especially of blue fibers. Fish farms are supplied with fresh water by rivers or streams, so it is possible that microplastics originate outside the fish farm, perhaps they were introduced due to high soil occupation, although surface runoff (of water contaminated by sewage) caused by heavy rains the most important factor. Therefore, one factor must be considered, surface runoff and groundwater contaminated by urban, agricultural and urban effluents may have contaminated rivers and streams and then contaminated the water in the fish farm ponds.